Karakteristik dan Evaluasi Prebiotik Tepung Biji Cempedak (Artocarpus champeden) - Ummul Khayrah; Endang Prangdimurti; Lilis Nuraida (Institut Pertanian Bogor, 2022)
This study aims to carry out chemical characterization and evaluate the prebiotic potential of cempedak (Arthocarpun champeden) seed flour. Cempedak seeds were processed by boiling and roasting, then dried and grinded. Boiled cempedak seed flour (BCF), roasted cempedak flour (RCF), and untreated cempedak seed flour (UCF) were analyzed proximately and measured the profiles of total starch and undigestable carbohydrates, which included resistant starch, total dietary fiber, insoluble dietary fiber, and soluble dietary fiber. Resistant starch content increased significantly (p<0.05) from 8% in UCF to 19% in BCF and RCF. Boiling and roasting treatments caused a decrease in SDF levels and an increase in IDF levels. The resistance of starch to hydrolysis by artificial gastric acid decreased after boiling. The value of prebiotic effect (PE) and prebiotic index (PI) showed a positive value of UCF on the growth of L. plantarum 1-S27202 (PE 0.27; PI 0.68) and the BCF on the growth of L. rhamnosus R23 (PE 0.18; PI 0.44). Keywords: Artocarpus champeden, chempedak seeds, resistant starch, dietary fiber, prebiotic